Why the Immune System Should Be Concerned by Nanomaterials? - Pallardy, Marc J.; Turbica, Isabelle; Biola-Vidamment, Armelle (Frontiers in Immunology, 2017)
Particles possess huge specific surface area and therefore nanomaterials exhibit unique characteristics, such as special physical properties and chemical hyper-reactivity, which make them particularly attractive but also raise numerous questions concerning their safety. Interactions of nanomaterials with the immune system can potentially lead to immunosuppression, hypersensitivity (allergy), immunogenicity and autoimmunity, involving both innate and adaptive immune responses. Inherent physical and chemical NP characteristics may influence their immunotoxicity, i.e. the adverse effects that can result from exposure. This review will focus on the possible interaction of nanomaterials including protein aggregates with the innate immune system with specific emphasis on antigen-presenting cells i.e dendritic cells, macrophages and monocytes.